Composite - its endless journey. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2009)
A composite, in its general term, is a solid material that results when two or more different substances, each with its own characteristics and properties, are combined to create a new substance whose properties are superior to those of the original components in a specific application, Composites are of greatest use in the aerospace industry in which their stiffness, lightness, and heat resistance make them the materials of choice in reinforcing the engine cowls, wings, doors, and flaps of aircraft. Composite materials are also used in rackets and other sports equipment, in cutting tools, and in certain parts of automotive engines.